1963
DOI: 10.1063/1.1729782
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Diffraction and Diffusion in Metal Film Layered Structures

Abstract: Artificial layered structures that produce sharp diffraction of x rays are described. The structures were made by alternately evaporating 140 Pb and Mg layers onto a glass slide (d=27 Å). The diffracting efficiency of the layered structures is compared with other structures used in soft x-ray spectroscopy. The usefulness of the structures is limited by diffusion in the layered system which caused the diffraction pattern to decay to half intensity in 2 days at room temperature. At 0°C the half life was 5 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1970
1970
2004
2004

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(9 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Measurement of interdiffusion in compositionally modulated multilayer structures using x-ray scattering is one technique to study diffusion lengths much shorter than the detection limit of sectioning and profiling techniques. [10][11][12][13] Several attempts have been made to study interdiffusion in chemically inhomogeneous multilayers. In a study by Mizoguchi et al, 14 interdiffusion and structural relaxation have been studied in 3d transition metal (TM)/Zr multilayers in the composition range of TM 67 Zr 33 using x-ray diffraction (XRD) technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of interdiffusion in compositionally modulated multilayer structures using x-ray scattering is one technique to study diffusion lengths much shorter than the detection limit of sectioning and profiling techniques. [10][11][12][13] Several attempts have been made to study interdiffusion in chemically inhomogeneous multilayers. In a study by Mizoguchi et al, 14 interdiffusion and structural relaxation have been studied in 3d transition metal (TM)/Zr multilayers in the composition range of TM 67 Zr 33 using x-ray diffraction (XRD) technique.…”
Section: Introductionmentioning
confidence: 99%
“…Neutron reflectivity is a nondestructive technique, which can be used for studying self-diffusion in a chemically homogeneous multilayer with a resolution as small as 0.1 nm, by taking advantage of isotopic labeling. Greer et al 10,16,17 have demonstrated the application of neutron reflectivity, measuring self-diffusion in amorphous NiZr multilayers. In another study by Baker et al 18 self-diffusion of amorphous 11 B on 10 B in isotopically enriched thin films of 11 B/ 10 B on Si was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The two components diffused into each other over a period of weeks. Thereafter some improvements were made on layered metal film optics for soft X-rays 34. Langmuir-Blodgett multilayers56 were created, using long-chain water insoluble fatty acid molecules.…”
Section: Multilayer Technique For X-raysmentioning
confidence: 99%
“…Thereafter some improvements were made on layered metal film optics for soft X-rays. 3,4 Langmuir-Blodgett multilayers 5,6 were created, using longchain water insoluble fatty acid molecules. As a result of technological limitations, further development and research progressed very slowly until the 1970s.…”
Section: Multilayer Technique For X-raysmentioning
confidence: 99%
“…The idea of an engineered selectable d-spacing analyzing crystal was, of course, well-known, following the work of DuMond and Youtz [19] in 1940 and Dinklage and Frericks in 1963 [20]. It was a time of innovation.…”
Section: X-ray Analysis In the 1970smentioning
confidence: 99%